Colonic wall thickness measured by ultrasound: striking differences in patients with cystic fibrosis versus healthy controls. Issue 3 (March 1997) - Haber, H P; Benda, N; Fitzke, G; Lang, A; Langenberg, M; Riethmüller, J; Stern, M
Abstract : BACKGROUND: Colonic strictures represent an advanced stage of fibrosing colonopathy in patients with cystic fibrosis. AIMS: To clarify whether ultrasonography can identify patients with an early stage of fibrosing colonopathy and to determine clinical factors that influence bowel wall thickening. PATIENTS: Ninety patients with cystic fibrosis, median age 10 years, and 46 healthy controls, median age 13 years, were investigated. METHODS: Bowel wall thickness was measured by ultrasound in a prospective study. RESULTS: In cystic fibrosis, wall thickness of both small intestine and colon was significantly (p < 0.0001) higher than in controls; 81% of patients with cystic fibrosis had a maximum colon wall thickness at any site of 2 mm or more, a value that was never reached by controls. The maximum colon wall thickness was 6.5 mm. Bowel wall thickness was unchanged at re-examination after one year. There was no progression even with high dose pancreatic supplements. There was no association between bowel wall thickness and clinical features such as previous meconium ileus, intestinal resection, distal intestinal obstruction syndrome, abdominal pain, or pancreatic enzyme dose. CONCLUSIONS: There is genuine intestinal involvement in cystic fibrosis; in a few cases this could lead to fibrosing colonopathy.